Care processes related to clinical detection of Alzheimer's disease in the U.S. Veterans Affairs Health Care System. (31st December 2021) - Miller, Donald R; Jasuja, Guneet; Davila, Heather W; Palnati, Madhuri; Shao, Qing; Dinesh, Deepika; McDannold, Sarah; Zhang, Quanwu; Monfared, Amir Abbas Tahami; Xia, Weiming; Palacios, Natalia; Moo, Lauren R.
Abstract: Background: Alzheimer's disease (AD) is a debilitating, progressive brain disorder that diminishes quality of life and represents immense burden of public health. This study characterizes healthcare utilization related to clinical detection of AD and care for AD patients in the US Veterans Affairs (VA) Healthcare System. Methods: Using the VA Corporate Data Warehouse (2000‐2019), we studied Veterans aged ≥50 years who received ≥2 ICD‐10 codes (G30) for AD, with first code appearing in fiscal year 2018. We identified prior related ICD‐10 codes and summarized care processes during the years before and the year after the first AD code, including referrals to dementia‐related medical specialists (neurologists, geriatricians, geriatric psychiatrists), assessments by neuropsychological tests and radiological brain imaging, dementia medication prescriptions (donepezil, galantamine, memantine, rivastigmine), community‐based services (home health, adult day programs), and placements in institutional long‐term care in VA or community nursing homes. Results: The study cohort consisted of 6, 046 Veterans (mean age of 80 years; 3% women; 22% non‐White race/ethnicity). Prior to the first ICD coding, 53.1% received codes for non‐specific dementia and 29.4% for mild cognitive impairment (MCI), with the first code appearing an average of 3 years before the first AD code. In the year before the first AD code, 51.1% visited specialists, 25.7% received neuropsychological assessments, 31.3% had brain imaging (but only 1.3% had a fluorodeoxyglucose‐PET scan), 30.2% received prescriptions for dementia medication, 45.8% received community‐based services, and 15.0% were admitted to institutional long‐term care. In the year following the initial AD code, 73.2% had specialty visits, 60.5% received dementia prescriptions, 63.6% received community‐based services, and 44.2% were admitted for institutional long‐term care. Conclusions: Medical and pharmacy utilization for non‐specific dementia or MCI begins years before AD detection, marked by the first AD‐specific clinical encounter in VA. Many AD patients do not receive specialty care and very few undergo a PET scan before AD detection. Community‐based home or day care and institutional nursing care increase with AD detection suggesting a substantial need for healthcare resources.